2019
DOI: 10.1007/s40472-019-00236-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver Bioengineering: Promise, Pitfalls, and Hurdles to Overcome

Abstract: Purpose of Review-In this review, we discuss the recent advancements in liver bioengineering and cell therapy and future advancements to improve the field towards clinical applications. Recent Findings-3D printing, hydrogel-based tissue fabrication, and the use of native decellularized liver extracellular matrix as a scaffold are used to develop whole or partial liver substitutes. The current focus is on developing a functional liver graft through achieving a nonleaky endothelium and a fully constructed bile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…To address the donor organ shortage, temporary procedures are developed to bridge the patients until transplantation, such as extracorporeal bioartificial livers, which still cannot compensate for the significant decline in the patients' quality of life (Kumar, Tripathi, & Jain, 2011). Another approach is hepatocyte transplantation, which is restricted by the low liver-engraftment rate and low survival rate of the transplanted hepatocytes (Ibars et al, 2016 with healthy liver cells such as primary or stem-cell-derived hepatocytes and nonparenchymal cells, especially with endothelial cells (Acun et al, 2019;Wang et al, 2017). The repopulation of the IHBDs, which is a critical component of the nonparenchymal population, has not been addressed in the engineered liver grafts until recently (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the donor organ shortage, temporary procedures are developed to bridge the patients until transplantation, such as extracorporeal bioartificial livers, which still cannot compensate for the significant decline in the patients' quality of life (Kumar, Tripathi, & Jain, 2011). Another approach is hepatocyte transplantation, which is restricted by the low liver-engraftment rate and low survival rate of the transplanted hepatocytes (Ibars et al, 2016 with healthy liver cells such as primary or stem-cell-derived hepatocytes and nonparenchymal cells, especially with endothelial cells (Acun et al, 2019;Wang et al, 2017). The repopulation of the IHBDs, which is a critical component of the nonparenchymal population, has not been addressed in the engineered liver grafts until recently (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in whole liver engineering hold the promise to create transplantable liver grafts by employing the native organ's extracellular matrix (ECM) as the template. In the whole liver engineering approach, the decellularized organ matrix is repopulated with healthy liver cells such as primary or stem‐cell‐derived hepatocytes and nonparenchymal cells, especially with endothelial cells (Acun et al, 2019; Wang et al, 2017). The repopulation of the IHBDs, which is a critical component of the nonparenchymal population, has not been addressed in the engineered liver grafts until recently (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, multiple cell therapy techniques developed to treat liver fibrosis/cirrhosis gathered knowledge about in vitro cell manipulation improvement and the mechanisms by which transplanted cells could reverse liver fibrosis and promote liver regeneration. This knowledge is now supporting the development of new approaches targeting the generation of in vitro systems that could lead to the development of liver organoids or even whole bioengineered livers for transplantation, aided by emerging sophisticated technologies like 3D (bio)printing, microfluidics, and bioreactors, as recently reviewed elsewhere [176].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that administrated cells developed aggregates that block the microvasculature system and led to uneven distribution of cells throughout the parenchyma when cells were introduced through the portal vein. In contrast, by cell transplantation through bile duct, these cells were uniformly distributed throughout decellularized hepatic parenchyma [134]. Some authorities declared the potency of decellularized non-hepatic bioscaffolds such as placental tissue for the restoration of hepatic function [135].…”
Section: Hepatic Differentiation Of Various Stem Cells On Decellularimentioning
confidence: 99%